2021
DOI: 10.1016/j.metabol.2021.154732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body composition on COVID-19 susceptibility and severity: A two-sample multivariable Mendelian randomization study

Abstract: Objectives Recent studies suggested obesity to be a possible risk factor for COVID-19 disease in the wake of the coronavirus (SARS-CoV-2) infection. However, the causality and especially the role of body fat distribution in this context is still unclear. Thus, using a univariable as well as multivariable two-sample Mendelian randomization (MR) approach, we investigated for the first time the causal impact of body composition on the susceptibility and severity of COVID-19. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 44 publications
5
65
1
1
Order By: Relevance
“…Interestingly, both BMI and waist circumference were associated with testing positive for COVID-19 in a dose-response fashion [ 30 ]. However, another study using a two-sample multivariable Mendelian randomization failed to show the impact of body composition (waist circumference, trunk fat ratio) on COVID-19 susceptibility and severity; only BMI was significant [ 31 ]. Our study has a limitation in that it did not include body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both BMI and waist circumference were associated with testing positive for COVID-19 in a dose-response fashion [ 30 ]. However, another study using a two-sample multivariable Mendelian randomization failed to show the impact of body composition (waist circumference, trunk fat ratio) on COVID-19 susceptibility and severity; only BMI was significant [ 31 ]. Our study has a limitation in that it did not include body composition.…”
Section: Discussionmentioning
confidence: 99%
“…However, gut dysbiosis by various factors has deleterious effects on host health, including the gastrointestinal tract [26] and immune system [27], and metabolic diseases [28]. The F/B ratio is known as a hallmark of obesity, and, interestingly, two recent studies have reported strong evidence for a causal impact of obesity on the susceptibility and severity of COVID-19 [29,30]. However, recent studies have reported no association between the F/B ratio and obesity [31].…”
Section: Discussionmentioning
confidence: 99%
“…The association of obesity-related traits with COVID-19 outcomes has been confirmed by multiple investigations, also including MR analyses that showed putative causal effects of BMI [9,10,11,41,42], WC [9,10], and trunk fat ratio [9]. Some of these previous investigations also have included MVMR analyses that highlighted how the effect of these traits on COVID-19 is independent of several cardiometabolic traits and other known risk factors [43]. However, to our knowledge, no study evaluated whether the effect of obesity-related traits on COVID-19 outcomes is independent of SES.…”
Section: Discussionmentioning
confidence: 87%
“…We estimated the putative causal effect of anthropometric traits on COVID-19 phenotypes using a two-sample MR approach. Leveraging information from genome-wide association statistics, we can estimate the putative causal effect of the exposure on the outcome, which represents the sum of all possible paths from the exposure on the outcome [9,34]. This analysis was conducted using the R package TwoSampleMR [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation